DO DIFFERENT WEIGHT TRAINING METHODS CHANGE THE APPETITE OF YOUNG ADULTS? - Thaliane Mayara Pessôa dos Prazeres; Rodrigo Ramalho Aniceto; Tércio Araújo do Rêgo Barros; Fábio Fellipe Martins de Lima; Ricardo Luís Fernandes Guerra; Wagner Luiz do Prado (Journal of Physical Education)
ABSTRACT This study assessed the effects of different weight training (WT) on appetite feeling in trained men. The sample consisted of 10 men aged between 18 to 29 years old. There were two experimental sessions with a wash out of seven days: in the circuit weight training (CWT), exercises were performed by alternating segment in stations, while during the traditional method (TM) exercises were performed in consecutive series. Both methods had the same total workload. The perception of hunger and perspective of food intake were measured in moments: at baseline, after exercise and 1 hour. Differences only in feelings of hunger among moment (p>0.05) were showed, and there were not differences between methods or effect of interaction (p>0.05). Thus, we concluded that both training methods are not altering the feeling of hunger or perspective of food intake, however the magnitude to raise is higher in TM.